Kombinasi Metode Entropy Dan Simple Additive Weighting (Saw) Dalam Penentuan Kepala Sekolah Terbaik - Rahmat Rahmat (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The education sector is one of the sectors that apply computerized information technology the most. This certainly has an impact on the continuous development of computer technology both in terms of hardware and software. One of the cases in the field of education that involves computers is the selection of the best principal using the decision support method. Decision support method is a method that can be used to provide recommendations on alternatives that have been previously determined based on predetermined criteria. In this study, a decision support model was developed using a combination of two methods, namely the Entropy and Simple Additive Weighting (SAW) methods. The entropy method is used to calculate the entropy value and normalized entropy, while the SAW method is used to normalize and rank alternatives based on the existing criteria. The results obtained are that the use of these two methods is considered better than using only one method, both entropy and SAW